2015
DOI: 10.1038/eye.2015.127
|View full text |Cite
|
Sign up to set email alerts
|

Literature review and meta-analysis of translaminar pressure difference in open-angle glaucoma

Abstract: There is increasing evidence in the literature regarding translaminar pressure difference's (TPD) role in the pathophysiology of glaucoma. The optic nerve is exposed not only to intraocular pressure in the eye, but also to intracranial pressure (ICP), as it is surrounded by cerebrospinal fluid in the subarachnoid space. Although pilot studies have identified the potential importance of TPD in glaucoma, limited available data currently prevent a comprehensive description of the role that TPD may have in glaucom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
2
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 77 publications
(136 reference statements)
1
24
2
2
Order By: Relevance
“…[19] However, this cross-sectional association is not supported by the current longitudinal analysis in our study. Using the YMES 5-year follow-up data, we did not find any significant association or trend between the baseline estimated CSFP and the incidence of POAG.…”
Section: Discussioncontrasting
confidence: 89%
“…[19] However, this cross-sectional association is not supported by the current longitudinal analysis in our study. Using the YMES 5-year follow-up data, we did not find any significant association or trend between the baseline estimated CSFP and the incidence of POAG.…”
Section: Discussioncontrasting
confidence: 89%
“…This hypothesis may also explain the increased incidence of glaucoma in patients with a history of migraine (Table 1), as elevated intracranial pressure is associated with this condition [164]. A recent literature review and meta-analysis comprising five papers and a total of 396 patients by Siaudvytyte et al revealed that CSFP is elevated in glaucoma patients compared to healthy subjects and TLPD is related to changes in optic disc structure in patients with high-tension glaucoma [162]. The authors caution, however, that further experimental investigations and longitudinal prospective clinical studies are required to overcome the methodological weaknesses of the current studies, concerns echoed by Pircher and Killer [138].…”
Section: Mechanisms Of Rgc and Axonal Deathmentioning
confidence: 99%
“…73 Studies have also reported that intracranial pressure is lower in patients with NTG than in those with POAG or normal subjects. 72,[74][75][76] Low intracranial pressure in the context of normal IOP levels might in fact lead to an abnormally large translaminar cribrosa pressure difference, thereby increasing the probability of glaucomatous damage. Jonas et al, 41 utilizing data from the Beijing Eye Study, reported that translaminar pressure difference (calculated with body mass index, diastolic blood pressure, and age) showed a better correlation with the extent of glaucomatous damage than did IOP, indicating its potential role as a biomarker for open-angle glaucoma.…”
Section: Translaminar Pressure Differencementioning
confidence: 98%